The Role of Micro Business Policies in Sport Tourism Development - Wuntu, Gana; Marhendi, Mengku; S.Pd. M.Si, Tutik; Raihan Hakim, Muhammad (Efficient: Indonesian Journal of Development Economics, 2025)
This study aims to analyze the effect of micro business model policy implementation and community readiness on the development of sport tourism in Cijagamulya, Ciawigebang District, Kuningan - West Java. The method used is quantitative approach with survey technique. Data were collected through questionnaires consisting of micro business actors, local communities, and related stakeholders. Data analysis was carried out using multiple linear regression to determine the relationship between independent and dependent variables. The research results show that the implementation of the micro business model policy and community readiness have a significant influence on the development of sport tourism. And based on SWOT analysis, the development of sport tourism in Cijagamulya is included in Quadrant I (Aggressive Strategy) which shows that the development of sport tourism has a strong position to continue to be developed. The results of this study confirm that the strengthening of sports tourism development in Cijagamulya is strongly influenced by the implementation of effective micro business model policies and the readiness of the community to support this sector.